Computer Aided Design of a Multi-Component Distillation Column for Processing of Nigerian Bonny Light Crude Oil - Kekpugile, Dagde Kenneth; Kilsibari, Kpalap Emmanuel (International Journal of Chemical and Process Engineering Research, 2016)
The design of the multi-component distillation column for processing of Bonny light crude is presented using advanced process simulation software (Aspen Hysys). The steady state design models were developed from Mesh equations and were used to obtain the design parameters based on the principle of conservation of mass and energy. The design parameters were column diameter, column cross sectional area, height of the column, downcomer area, hole area, weir length, wet area and tray spacing. The equations developed are capable of predicting compositions, partial pressures and temperature of the components of interest from the mixtures of crude oil. The accuracy of the design parameters were ascertained by comparing predicted results with literature data of a distillation unit. The simulation of the design models were performed using Aspen Hysys to obtain optimum values of the most significant variables/parameters (column diameters 1.558m, column height 17.048m, cross section area 1.907m2, downcomer area 0.229m2, tray spacing 0.5m, weir length 1.200m, hole area 0.191m2 and wet area 1.678m2). The result obtained from the steady state simulation shows that the feed flow rate, temperature and pressure influence the efficiency of the distillation column.